Evaluation of Guided Bone Regeneration Using Xenograft/APRF Mixture in Atrophic Posterior Mandible (Clinical and Radiographic study) - Richa, Ramy; Osman, Essam; Attia, Nahed; Arakji, Hani; Shokry, Mohamed (European Scientific Journal, ESJ, 2023)
Introduction: The rehabilitation of posterior mandible with dental implants represents today a hard challenge for clinicians due to the lack of supporting bone. Different surgical techniques are currently being used to augment the posterior mandible where GBR is considered most commonly used. Materials and Methods: Fifteen patients were selected to treat mandibular alveolar ridge resorption with guided bone regeneration using titanium reinforced membrane and a filling mixture of xenograft bovine bone/PRF. The membrane was fixed using meisinger pin control kit and profix 3mm microscrews. A PRF membrane was used to cover the Ti d-ptfe. Results: Using the mixture of PRF/xenograft as well as PRF membranes showed promising results in term of primary wound healing, whereas a significant bone quantity with a mean bone volume of 5.78 ± 0.81 was reported. The primary implant stability recorded high values and significantly increased at a period of 6 months post insertion p=0.037 Conclusion: It could be concluded that PFR/ xenograft mixture can be promising when used with the titanium reinforced d-ptfe membrane in 3D ridge reconstruction of atrophic posterior mandible, moreover using PRF membrane to cover the TI- d-ptfe membrane could enhance soft tissue healing as well as it can prevent soft tissue dehiscence due to the concentration of the growth factors that can be released during primary wound healing. Xenograft/PRf mixture can be consistent to be utilized for creation of new bone in severely atrophic ridges if used in GBR. The high ISQ at primary implant placement and at a period of 6 months post insertion according to Osstell can explain the successful application of this mixture in 3D bone augmentation of atrophic posterior mandible.